2017
DOI: 10.2134/agronj2016.01.0044
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Use Efficiency and Yield Response of High Biomass Sorghum in the Lower Midwest

Abstract: Core Ideas Two‐year study evaluating high biomass sorghum yield response to a broad range of N treatments. A minimal N fertilizer rate of 56 kg ha−1 is needed to increase average ethanol yield to 5519 L ha−1, with no additional yield benefit at greater N rates. Yields were limited by varying environmental conditions and delayed planting. Nitrogen recovery efficiency were greatest at low N rates, but N use efficiency more stable across N rates, but greatly impacted by environment. High biomass sorghum [Sorghum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
17
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 28 publications
10
17
1
1
Order By: Relevance
“…These trends match those of previous studies on grain sorghum NUE (Gardner et al, 1994; Zweifel et al, 1987), which decrease with increasing plant N concentration. Similarly, in a concurrent study to this one, high biomass sorghum NUE was observed to decrease at 56N or greater (Maw et al, 2017b).…”
Section: Resultssupporting
confidence: 57%
“…These trends match those of previous studies on grain sorghum NUE (Gardner et al, 1994; Zweifel et al, 1987), which decrease with increasing plant N concentration. Similarly, in a concurrent study to this one, high biomass sorghum NUE was observed to decrease at 56N or greater (Maw et al, 2017b).…”
Section: Resultssupporting
confidence: 57%
“…The stem component accounted for 79% of total increase of crop N as a function of increasing N fertilization rate. A similar trend with greater stem N content response due to greater N fertilization rate was reported by Maw et al (2017) for cultivars ES5200 and ES5201 and by Ameen et al (2017) for cultivar Guoneng-11;however, Ameen et al (2017) also reported, in 1 out of 2 yr, greater stem P (from 6 to 11 kg ha -1 ) and K (from 39 to 68 kg ha -1 ) content as a function of increasing N fertilization rate.…”
Section: Biomass Sorghum Stem Yield Nutrient Content and Plant Heightsupporting
confidence: 68%
“…There was no N fertilization rate effect on N, P, or K leaf content observed in our study. In contrast, Maw et al (2017) and Ameen et al (2017) reported leaf nutrient content effects as a function of N fertilization in 1 out of 2 yr. The year × N rate interaction effect for leaf P content occurred because P content between years was not different at the 0-N rate only compared with the other four rates that were greater in 2014 ( Table 2).…”
Section: Leaf Yield and Nutrient Contentmentioning
confidence: 90%
See 2 more Smart Citations